A new role in a new world: when an Osing traditional musicians become a teachers - Karsono Karsono (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
Global socio-cultural changes have significantly impacted traditional cultural life in various regions. In Banyuwangi, East Java, global cultural changes have influenced the lifestyle of the Osing community, the indigenous people of Banyuwangi. One of the cultural changes among the Osing is the shift in economic systems from agrarian-maritime to industrial. This change has eroded the socio-cultural space of traditional performing arts. The situation has led traditional artists, especially Osing traditional musicians, to face an existential crisis regarding their roles and functions. Traditional art performances, particularly traditional music, which used to be their space for expression in society, are now rare. This has led to a reduction in the intensity and frequency of work for Osing traditional musicians. This research aims to demonstrate and explain the new role of Osing traditional musicians in preserving and reaffirming their existence through their roles as music teachers in formal schools. The study adopts an ethnomusicological approach using observation, interviews, and documentation methods. Ethnographic analysis of the data indicates that the new role of Osing traditional musicians as music teachers in formal schools has emerged due to the limited role they play in traditional performances. In such circumstances, a paradoxical situation arises. On one hand, industrialization weakens traditional arts, leading to an existential crisis for musicians as stage performers. On the other hand, the government's awareness of the need to preserve cultural identity in the global arena requires strengthening cultural heritage through education, which cannot solely rely on formal school teachers. This is where Osing traditional musicians seize the opportunity to take on roles as teachers in formal schools. As a result, the role of traditional musicians remains relevant, and the inheritance of Osing traditional music culture is preserved and sustainable.